Student Behavior Character in School - Amin, Zulkifli (Indonesian Journal Education, 2023)
In the era of globalization and information openness which is so widespread in all corners of the earth. Where the barriers to isolated information have been opened as wide as possible, such a state of information has also hit our world of education so that it has entered our schools. The information that is spread is not only scientific about the lesson but also entertainment, sports and some are even negative. School age is an age that is very vulnerable to this information. In the independent curriculum, it is quite clear about the Pancasila Student Profile, where lately, the problem of character has become a separate problem among students at school. As we all know that there are many criminal incidents, it turns out that many are committed at school age, namely between the ages of 14-17 years. The importance of instilling character among students at school is the main thing, considering the life of these students is a transitional period, where they enter a world which so far has only been confined to the family, while their thinking develops and the real world they face needs provisions that seriously given so that they can withstand or have a stronghold of self-defense in this era of globalization. The cultivation of this character can be done with habits that are carried out at school at any time, such as implementing K3 (Cleanliness, Beauty and Order). Also the discipline of the teachers